A₁+a₄=2 a₁²+a₄²=20 S₈=?
Возведём в квадрат обе части первого уравнения:
(a₁+a₄)²=2²
a₁²+2*a₁*a₄+a₄²=4
a₁²+a₄²=20
Вычитаем из первого уравнения второе:
2*a₁*a₄=-16
a₁*a₄=-8 a₁*(2-a₁)=-8 2a₁-a²=-8 a₁²-2a₁-8=0 D=36 a₁=4 a₁=-2
a₁+a₄=2 a₄=2-a₁ a₄=-2 a₄=4
1) a₁=4 a₄=-2
a₁+a₄=a₁+a₁+3d=2a₁+3d=2*4+3d=8+3d=2 3d=-6 d=-2
a₈=a₁+7d=4+7*(-2)=4-14=-10
S₈`=(a₁+a₈)*n/2=(4+(-10))*8/2=-6*4=-24.
2) a₁=-2 a₄=4
a₁+a₄=2 a₁+a₁+3d=2a₁+3d=2*(-2)+3d=-4+3d=2 3d=6 d=2
a₈=a₁+7d=-2+7*2=12
S₈``=(a₁+a₈)*n/2=(-2+12)*8/2=10*4=40.
Ответ: S₈`=-24 S₈``=40.